2020
DOI: 10.1371/journal.pgen.1008324
|View full text |Cite
|
Sign up to set email alerts
|

The plant mobile domain proteins MAIN and MAIL1 interact with the phosphatase PP7L to regulate gene expression and silence transposable elements in Arabidopsis thaliana

Abstract: Transposable elements (TEs) are DNA repeats that must remain silenced to ensure cell integrity. Several epigenetic pathways including DNA methylation and histone modifications are involved in the silencing of TEs, and in the regulation of gene expression. In Arabidopsis thaliana, the TE-derived plant mobile domain (PMD) proteins have been involved in TE silencing, genome stability, and control of developmental processes. Using a forward genetic screen, we found that the PMD protein MAINTENANCE OF MERISTEMS (MA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Later, it was shown that MAIN and MAIL1 were required for the proper expression of a common subset of genes, as well as TE silencing [ 104 ] ( Figure 1 D). MAIN and MAIL1 physically interact together, as well as with a putative serine/threonine phosphoprotein phosphatase (PPP) called PP7-LIKE (PP7L), and the three mutants show similar developmental and molecular phenotypes, including TE silencing defects [ 107 , 108 ]. Genome-wide level of 5mC is mostly unchanged in main and mail1 mutants, with the notable exception of a slight increase in CHG methylation at pericentromeric regions and in chromosome arm TEs [ 108 ].…”
Section: A Plethora Of Sophisticated Epigenetic Pathways Dampen Tesmentioning
confidence: 99%
See 4 more Smart Citations
“…Later, it was shown that MAIN and MAIL1 were required for the proper expression of a common subset of genes, as well as TE silencing [ 104 ] ( Figure 1 D). MAIN and MAIL1 physically interact together, as well as with a putative serine/threonine phosphoprotein phosphatase (PPP) called PP7-LIKE (PP7L), and the three mutants show similar developmental and molecular phenotypes, including TE silencing defects [ 107 , 108 ]. Genome-wide level of 5mC is mostly unchanged in main and mail1 mutants, with the notable exception of a slight increase in CHG methylation at pericentromeric regions and in chromosome arm TEs [ 108 ].…”
Section: A Plethora Of Sophisticated Epigenetic Pathways Dampen Tesmentioning
confidence: 99%
“…MAIN and MAIL1 physically interact together, as well as with a putative serine/threonine phosphoprotein phosphatase (PPP) called PP7-LIKE (PP7L), and the three mutants show similar developmental and molecular phenotypes, including TE silencing defects [ 107 , 108 ]. Genome-wide level of 5mC is mostly unchanged in main and mail1 mutants, with the notable exception of a slight increase in CHG methylation at pericentromeric regions and in chromosome arm TEs [ 108 ]. Importantly, this modest non-CG hypermethylation does not correlate with changes in TE expression observed in the mutant [ 108 ].…”
Section: A Plethora Of Sophisticated Epigenetic Pathways Dampen Tesmentioning
confidence: 99%
See 3 more Smart Citations